Improving The Skills of Prospective Social Workers in Improving Social Services for Disabled Groups Through Sign Language Training - Siregar, Hairani; Nur. R, Siti Hazzah (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
USU's Social Welfare Study Program is a study program that prepares social workers. Law Number 14 of 2019 concerning Social Workers states that a social worker is someone who has the knowledge, skills and values of social work practice and gets a certificate of competence. In carrying out social work practices based on a)non-discriminatory, b)solidarity c)justice d)professionalism e)expediency f)cohesiveness g)partnership h)accessibility and i)accountability. As a prospective professional social worker, you must prepare yourself to provide social services to everyone without exception. This includes providing social services to persons with disabilities. One type of disability is a group that has hearing loss or can't hear at all, who are often called deaf or deaf people. They have difficulty communicating with listeners. Therefore a social worker must be able to understand or communicate with deaf people. The Mono Community Service Program 2021 with the title Improving Skills of Prospective Social Workers in Improving Social Services for Disabilities Groups Through Sign Language Training has started in August with training methods conducted face-to-face and via zoom. The trainess, who are students of the Social Welfare Study Program, already understand the culture of the deaf and can practice short letters and words using sign language.